Double summation

Algebra Level 4

Find the value of

m = 1 n = 1 m n 2 2 n ( n 2 m + m 2 n ) \displaystyle\sum_{m=1}^\infty \displaystyle\sum_{n=1}^\infty \frac{mn^2}{2^n(n2^m+m2^n)}

Note : do NOT use wolfram alpha


The answer is 2.00.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Hasan Kassim
Nov 27, 2014

We have:

I = m = 1 n = 1 m n 2 2 n ( n 2 m + m 2 n ) \displaystyle I= \sum_{m=1}^{\infty} \sum_{n=1}^{\infty} \frac{mn^2}{2^n(n2^m+m2^n)}

= m = 1 n = 1 m n 2 4 n 2 m ( n 2 n + m 2 m ) \displaystyle = \sum_{m=1}^{\infty} \sum_{n=1}^{\infty} \frac{mn^2}{4^n2^m(\frac{n}{2^n}+\frac{m}{2^m})} (Divide by 2 m 2 n 2^m2^n ).

Now:

2 I = m = 1 n = 1 m n 2 4 n 2 m ( n 2 n + m 2 m ) + m = 1 n = 1 n m 2 4 m 2 n ( m 2 m + n 2 n ) \displaystyle 2I= \sum_{m=1}^{\infty} \sum_{n=1}^{\infty} \frac{mn^2}{4^n2^m(\frac{n}{2^n}+\frac{m}{2^m})} + \sum_{m=1}^{\infty} \sum_{n=1}^{\infty} \frac{nm^2}{4^m2^n(\frac{m}{2^m}+\frac{n}{2^n})}

= m = 1 n = 1 m n 2 4 n 2 m ( n 2 n + m 2 m ) + n m 2 4 m 2 n ( m 2 m + n 2 n ) \displaystyle = \sum_{m=1}^{\infty} \sum_{n=1}^{\infty} \frac{mn^2}{4^n2^m(\frac{n}{2^n}+\frac{m}{2^m})}+\frac{nm^2}{4^m2^n(\frac{m}{2^m}+\frac{n}{2^n})}

= m = 1 n = 1 m n 2 m 2 n m 2 m + n 2 n ( n 2 n + m 2 m ) \displaystyle = \sum_{m=1}^{\infty} \sum_{n=1}^{\infty} \frac{\frac{mn}{2^m2^n}}{\frac{m}{2^m}+\frac{n}{2^n}} (\frac{n}{2^n}+\frac{m}{2^m})

= m = 1 n = 1 m n 2 m 2 n \displaystyle = \sum_{m=1}^{\infty} \sum_{n=1}^{\infty} \frac{mn}{2^m2^n}

= ( m = 1 m 2 m ) 2 \displaystyle = (\sum_{m=1}^{\infty} \frac{m}{2^m} )^2

The last series can be derived from the geometric series :

k = 1 x k = x 1 x \displaystyle \sum_{k=1}^{\infty} x^k = \frac{x}{1-x} where x ] 1 , 1 [ x\in ]-1,1[

Differentiate both sides:

k = 1 k x k 1 = 1 ( 1 x ) 2 \displaystyle \sum_{k=1}^{\infty} kx^{k-1} = \frac{1}{(1-x)^2}

Multiply by x x :

k = 1 k x k = x ( 1 x ) 2 \boxed{\displaystyle \sum_{k=1}^{\infty} kx^k = \frac{x}{(1-x)^2} }

Therefore:

2 I = ( m = 1 m ( 1 2 ) m ) 2 = ( 1 2 ( 1 1 2 ) 2 ) 2 = 4 \displaystyle 2I= (\sum_{m=1}^{\infty} m(\frac{1}{2})^m )^2 = (\frac{\frac{1}{2}}{(1-\frac{1}{2})^2})^2 = 4

Hence, I = 2 \boxed{I=2} .

Your division at the beginning is pointless. Just add them together.

A Former Brilliant Member - 6 years, 6 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...